(untitled) (Research, Society and Development, 2025)
Introduction: Post-dural puncture headache (PDPH) is a common complication after dural puncture, affecting patients’ quality of life. Epidural blood patch (EBP) is a therapeutic option, but controversies remain regarding its effectiveness compared to other approaches. Objective: To evaluate the efficacy of EBP compared to other treatments in the management of PDPH in adults, defining its pathophysiology and comparing pain relief, time to symptom resolution, and occurrence of complications in patients treated with EBP versus peripheral nerve block or autologous platelet-rich fibrin (i-PRF). Methods: A systematic review was conducted in PubMed and SciELO databases, using the PICO strategy to identify relevant studies published between 2020 and 2025. Inclusion and exclusion criteria were rigorously applied, resulting in a final sample of five articles. Results and Discussion: Observational studies suggested that peripheral nerve blocks, such as greater occipital nerve block and sphenopalatine ganglion block, may be safe and effective alternatives for patients who do not respond to conservative treatment or as adjuvants to partial EBP. The use of i-PRF patches also showed promising results in reducing pain, especially in cases resistant to EBP. Conclusion: EBP remains the safest and most effective intervention for current clinical practice in the management of PDPH. However, further randomized clinical trials with greater methodological rigor are needed to consolidate equivalent alternatives in terms of efficacy and safety.